Response of Santa Maria’ Pear Budlings Grown on Two Rootstocks to Soil Application of FeEDDHA - AHMED, HUSAIN S.; HASSABALLA, ISSAM A.; SHALADAN, MOHAMED S. (The Libyan Journal of Agriculture, 2023)
Young ‘Santa Maria’ pear (Pyrus communis L.) plants grown on quince (Cydonia oblonga Mill) and Pyrus betulaefolia Bunge, rootstocks, were soil treated with five different rates of iron chelate, FeEDDHA (0, 5, 10, 15 and 20 grams/plant), to correct for a possible lime-induced iron chlorosis. The FeEDDHA treatments checked iron chlorosis within 2-3 weeks of application and stimulated trunk and vegetative growth. Plants grown on betulaefolia rootstocks were more vigorous, and suffered less chlorosis than those grown on quince. Untreated plants suffered severe leaf burning, especially on quince rootstock.